Ibn al-Haytham - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
Ibn al-Haytham was born Abu Ali al-Hassan ibn al-Hassan ibn al-Haytham in Basra (Iraq) in 965 A.D. He is known in Europe as Alhazen or Alhacen.